Platform decay - Wells, Martha (Wells, Martha. Murderbot diaries, 2026)
Everyone's favorite lethal SecUnit is back in the next installment of Martha Wells' bestselling and award-winning Murderbot Diaries series. Having someone else support your bad decision feels kind of good. After volunteering to run a rescue mission, Murderbot realizes that it will have to spend significant time with a bunch of humans it doesn't know. Including human children. Ugh. This may well call for... eye contact! (Emotion check: Oh, for f-) -- Provided by publisher.